Tax Planning, Deferred Tax Expense and Deferred Tax Assets on Earnings Management - Rafika Anwar (Advances in Taxation Research, 2023)
This study aims to determine the effect of tax planning, deferred tax expense, and deferred tax assets on earnings management. Earnings Management is an action taken by management in an effort to increase or decrease profits in the financial statements. This study uses statistical analysis methods. The data collection method used in this research is documentation. The data collection process in this study was carried out by taking data from the financial statements of mining companies listed on the Indonesia Stock Exchange in 2016-2019. The data analysis tool in this study uses the IBM SPS application. The results of the study found that: Tax planning has a positive and significant effect, earnings management in tax planning is carried out with the aim of maximizing the profits obtained after calculating taxes. Deferred tax expense has a positive and insignificant effect, temporary differences due to deferred tax expense give rise to management discretion in applying the principles or assumptions in the financial statements. Deferred tax assets have a negative and insignificant effect, the implementation of earnings management through deferred tax assets is considered to cause losses and the financial statements are considered dubious.